2. Winter Sport Olympiade - Meiseimann, Harnisch (Sozialistische Arbeitersport-Internationale, 1931)
Painting of stylized skier in snow Poster advertising sport event held in Mürzzuschlag, Austria, 5-8 February, 1931 PO-0764